Tathir Istikhdam Namudhaj Altaelim Somatic, Auditory, Visualization, Intelektual, Litarqiat Alkitabah Ladaa Tulaab fil Madrasah Al Mutawasitat Al-islamiah ahliyah Al-Manar batu Hambar Payakumbuh - suci yulianti; fajriyani arsya (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2026)
The problems identified in Arabic language learning among students at Al-Manar Private Islamic Junior High School, Batuhampar, Payakumbuh include the low learning outcomes in Arabic, particularly in writing skills, and the continued use of traditional teaching models by teachers. The objectives of this study were to determine the implementation of the SAVI (Somatic, Auditory, Visualization, Intellectual) learning model in improving students’ writing skills and to examine its effect on seventh-grade students’ writing skills. This study employed a quantitative approach with an experimental design. The research design used was the Pretest-Posttest Control Group Design. The results of the study indicate that there is an effect of the learning model on students’ Arabic learning outcomes, especially in writing skills at Al-Manar Private Islamic Junior High School, Batuhampar, Payakumbuh. The post-test results in the control class showed an average score of 70.32, while the experimental class achieved an average score of 89.48, with a mean difference of 19.16. Based on the hypothesis testing using the t-test, the calculated t-value (6.868) was greater than the t-table value (2.010), indicating that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected.